Type 2 diabetes mellitus and recent treatment options in adolescents and young adults - Md Nadeem Bari; Md Rizwan Ansari; Mohammad Anwar; Imran Mohammad (Faculty of Medicine, Universitas Trisakti, 2025)
Although type 2 diabetes mellitus (T2DM) has historically been thought of as a disease that mostly affects adults, its incidence among adolescents and young people has been rising in tandem with the rising rates of childhood obesity. There is no evidence to support the best course of treatment for T2DM in this age group despite the undeniable benefits of lifestyle adjustment for obese kids. Early diabetes start is linked to extended exposure to the disease and a greater likelihood of chronic issues, which impact more individuals during their working years and highlight the negative social effects of the condition. Additionally, there is mounting evidence that juvenile diabetes cohorts exhibit an aggressive phenotype that contributes to the early onset of problems that negatively affect life quality and negatively impact long-term results, increasing the possibility of a future public health emergency. Relevant studies were identified through a systematic search of PubMed, ScienceDirect, and Google Scholar for articles published between 2019 and 2025 using the keyword “Adolescents and (T2DM or Insulin Resistance)”. Type 2 diabetes in young people is a serious global public health issue now. Many significant obstacles must be overcome to treat T2DM that develops in young people, including a lack of effective treatment alternatives and limitations in carrying out therapeutic research. The US Food and Drug Administration has approved metformin, glimepiride (Amaryl), and insulin as treatments for teenagers and young adults with type 2 diabetes, despite therapeutic medication studies. Given modified pharmaceutical laws, it is probable that further anti-diabetic drugs will be included in the arsenal of treatment choices available to teenagers and young adults with T2DM. The epidemiology and current understanding of the pathophysiology, risk factors, consequences, and therapy of T2DM in adolescents and young adults are discussed in this review.